Beneficial Effect on Exercise Tolerance of a Comprehensive Rehabilitation Program in Elderly Obese Patients Affected With Heart Disease - Gondoni, Luca Alessandro; Nibbio, Ferruccio; Titon, Annamaria (Frontiers in Cardiovascular Medicine, 2021)
Aims: The number of elderly patients affected with multiple chronic diseases is constantly increasing. Even though multiple studies demonstrated a beneficial effect of cardiac rehabilitation, we don’t have data on the outcomes in elderly patients with obesity and heart disease. Methods: We studied 772 consecutive obese subjects (275 women; 35.6%) aged ≥ 70 years, affected with coronary artery disease and/or heart failure. We conducted a symptom limited exercise test at the beginning and at the end of the program which consisted of aerobic and strength physical activity, diet, and psychological counseling. Results: Mean BMI at baseline was 37.6 ± 4.4 kg/m2 and decreased to 36.4 ± 4.3 kg/m2 (P < 0.001). At baseline, attained METs were 4.7 ± 1.7, and by the end of the program were 5.6 ± 2.1 (P < 0.001). The mean improvement was 21.6 ± 21.7% (median 17.6%, 95% CI 20.0 – 23.1%). Patients over 80 years old had similar results compared to the younger ones. Diabetics did worse than non-diabetic patients: the improvement they reached was 19.4 ± 18.9% vs 23.8 ± 23.9% (P = 0.005). The presence of heart failure was significantly related to both the baseline and final performance, but the attained improvement was significantly greater in heart failure patients: 24.3 ± 23.8% vs 16.3 ± 15.4% (P < 0.001). No patient had adverse events related to the program. Conclusion: This study documents a significant improvement in exercise capacity in elderly obese patients affected with heart disease who underwent a rehabilitation program.